Respuesta :
Bring the minus 3 to the other side somit becomes +3 so you get p =+3-4
So p=-1
Hope this helps:)
Don’t forget to mark as brainliest if you thought it was most helpful:)
So p=-1
Hope this helps:)
Don’t forget to mark as brainliest if you thought it was most helpful:)
In p - 3 = -4
We need to move the constants to one side so
P - 3 = -4 becomes
P -3 +3 = -4 +3 which becomes
P = -1
The correct answer would be p = -1
I hope this helps! <3 Please mark as brainliest if most helpful :)
We need to move the constants to one side so
P - 3 = -4 becomes
P -3 +3 = -4 +3 which becomes
P = -1
The correct answer would be p = -1
I hope this helps! <3 Please mark as brainliest if most helpful :)